Hacer divorcio en España en los inicios del siglo XX - Rosa Mª Capel Martínez (Cahiers de Civilisation Espagnole Contemporaine)
Marriage has always been a central element of family and social organization. In Catholic Spain at the beginning of the 20th century, it was mostly understood as the monogamous, enduring and indissoluble union of a man and a woman. Consequently, divorce was something dangerous and condemnable, because it broke the established order and caused great harm to individuals, families and societies. However, there were undeniable conflicts within the homes that needed to be resolved. Women, who were recommended to submit, were the ones who bore the brunt in such situations. Divorce could be a solution, but resistance to its practice, even in the most obvious cases and not affecting the bond, turned the path to separation into an obstacle course that required strength of character, support and resources to overcome them. Still, success was not guaranteed. The three cases of female lawsuits that we analyzed show us this.